SEHAT DI USIA REMAJA MELALUI PEMBINAAN DAN PEMANTAUAN KESEHATAN SECARA RUTIN - Hendy Suwibowo (Abdi Seni, 2016)
The teens' behavior often invite attention, show egocentricity and attempt to present a desire to appear. The teens have many potencies and it must be managed so that they use it for the right deeds. Based on the reason, then, the writer holds community service entitled "Sehat Diusia Remaja Melalui Pembinaan dan Pemantauan Kesehatan Secara Rutin" ( Health at the Teens Through a Routine Health Management and Monitoring). The program is held in Sekolah Menengah Kejuruan Negeri 8 Surakarta because it is never given before in the school. The method used in the community service in SMKN 8 Surakarta is speech, action, and demonstration. The method used has advantages for it is a combination of some manners for one activity. It is supposed to optimalize activities of respiratory sports._The result getfram the program covers the increasing of I) technical skill of respiratory sports for students in SMKN 8 Surakarta; (2) knowledge about health function; and (3)  knowledge concerning treatment in behaviour, sanity and the substance abuse. The impact of the activity include: (1) burningfat (2) noteasily wrinkles; (3) avoidedfrom asthma bronchiale desease and respiratory disorders because of liquid accumulation in the lungs; and (4) the increasing of public interest towards respiratory sports.Key words: young, health, sport